Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan Pada PT. Bank Sulselbar Cabang Pare-Pare - Diana Sari; Abdullah Abdullah; Baharuddin Baharuddin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to find out the influence of organizational culture on employee performance at PT. Bank Sulselbar Pare-Pare Branch. The type of research used is quantitative with primary data sources and data collection through questionnaire instruments from a simple randomly drawn sample of 36 respondents, and analyzed using simple regression. The research results show that organizational culture has a positive and significant influence on employee performance at PT Bank Sulselbar Pare-Pare Branch. Therefore, the hypothesis proposed in this research is proven and accepted.